2003
DOI: 10.1148/rg.234025083
|View full text |Cite
|
Sign up to set email alerts
|

Missed Breast Carcinoma: Pitfalls and Pearls

Abstract: Mammography is the standard of reference for the detection of breast carcinoma, yet 10%-30% of breast cancers may be missed at mammography. Possible causes for missed breast cancers include dense parenchyma obscuring a lesion, poor positioning or technique, perception error, incorrect interpretation of a suspect finding, subtle features of malignancy, and slow growth of a lesion. Recent studies have emphasized the use of alternative imaging modalities to detect and diagnose breast carcinoma, including ultrason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(121 citation statements)
references
References 30 publications
2
113
0
6
Order By: Relevance
“…Mammography has been established as the primary and standard imaging screening method for breast cancer detection since its superiority was recognised when compared to clinical breast examination (CBE) and breast self-examination (BSE) (Majid et al, 2003). One study reported that the sensitivity and specificity of mammography in detecting invasive breast cancer was 33.3% and 95.0% respectively.…”
Section: Practice and Barriers Of Mammography Among Malaysian Women Imentioning
confidence: 99%
“…Mammography has been established as the primary and standard imaging screening method for breast cancer detection since its superiority was recognised when compared to clinical breast examination (CBE) and breast self-examination (BSE) (Majid et al, 2003). One study reported that the sensitivity and specificity of mammography in detecting invasive breast cancer was 33.3% and 95.0% respectively.…”
Section: Practice and Barriers Of Mammography Among Malaysian Women Imentioning
confidence: 99%
“…The degree of enhancement is thought to be proportional to the vascularity and hence the suspected grade of the tumor. 2,5 Benign tumors, however, may also enhance. By taking note of the enhancement as a function of time, one can distinguish, in many cases, between benign and malignant lesions.…”
Section: 3mentioning
confidence: 99%
“…Breast cancer is the most prevalent cancer in women and is the second leading cause of cancer deaths in women (7). In North America, screening mammography has a false negative rate of 20 to 30% (8,9) and a recall rate of about 10% (10). With a disease prevalence of about 0.3% (11), the vast majority of those recalled will not have cancer.…”
mentioning
confidence: 99%